Kedudukan Al-Quran dan Hadis sebagai Dasar Pendidikan Islam - Kirtawadi, Kirtawadi (Prodi Pendidikan Agama Islam IAINU Kebumen, 2023)
Islamic education is a very urgent matter in life for all mankind. This is because Islamic education is a means for all humans to achieve their life goals, namely to achieve happiness in this world and the hereafter. The foundation of Islamic education which is the main reference is two things, namely the Koran and hadith. So the article written by the author wants to reveal the position of the Koran and Hadith for Islamic education. The research method used by the author uses literature study research, namely a series of activities carried out by the author with regard to data collection methods that focus on the bibliography, by reading, taking notes and then managing the necessary data. So that this method can reveal the position of the Koran and Hadith as the basis of Islamic education. The results of this research show that the position of the Al-Qur'an and Hadith in Islamic education have similarities between the two, namely that both are the main references in Islamic education, but they also have differences. Because the Koran is a global revelation. So to understand it requires interpretation. Meanwhile, hadiths function to provide explanations for the concepts contained in the Qur'an, including education, and serve as role models.